The Hard Power Limitation: The Failure of Russia to Bring Back the Great Power Status - Sungkar, Najmi; Avianto, Wishnu; Syawfi, Idil (Jurnal Sentris, 2024)
This journal provides a comprehensive examination of the evolving dynamics surrounding Russia's rise in global power and the challenges it encounters in aligning with Vladimir Putin's vision. By using the Smart Power concept, which uses military power and diplomacy to achieve goals on the international stage, it is known as "Smart power". We examine how Russia has become more dominant in the military, economic and energy sectors over the past 20 years. However, Russia's influence is not as great as expected despite progress. Russia’s strong military capabilities could neither create fear of the enemy nor form friendship as it should. In addition, this country's economy does not get the full benefits of alliances with other countries. Furthermore, Russia finds it difficultto build trust with other countries because Russia tendsto use violence ratherthan discussions disguised in diplomacy. This analysis reveals a complex picture of Russia's future, highlighting the need to bridge the gap between hard and soft power in order to have a more unified and influential presence in the international stage. Keywords: Russia, Hard Power, Soft Power, Military, Economy, Diplomacy